Impact of iron chelation therapy on mitochondrial function, vascular integrity and inflammation in transfusion-dependent myelodysplastic syndromes - García-Delgado, Regina; Moreno-Carrasco, Gloria; Carrasco-Gomariz, Manuel; García-Segovia, Silvia; Flores, Rodolfo Matías Ortiz; Torres-González, Julio; Gallego-Fuillerat, Gonzalo; López-Villodres, Juan Antonio; Escamilla-Sánchez, Alejandro (Frontiers in Immunology, 2025)
BackgroundPatients with myelodysplastic syndromes (MDS) frequently develop chronic transfusion dependence, leading to progressive iron overload. This accumulation of non-transferrin-bound iron (NTBI) contributes to oxidative stress, mitochondrial dysfunction, endothelial damage, impaired vascular regeneration, and heightened inflammation.ObjectivesTo assess whether iron chelation therapy can reverse cellular and vascular injury, redox imbalance, and immune dysfunction in transfusion-dependent MDS patients.MethodsPeripheral blood from 23 transfusion-dependent MDS patients was analysed in a paired pre-/post-treatment design. Patients received daily oral deferasirox at standard clinical dosing for approximately 6 months (median). Flow cytometry was employed to evaluate reactive oxygen species (ROS), expression of adhesion molecules, mitochondrial membrane potential, circulating endothelial progenitor cells (EPCs), and intracellular levels of key pro-inflammatory cytokines.ResultsChelation therapy was associated with a ~55% decrease in serum ferritin and robust redox recovery: leukocyte H2O2 and superoxide decreased ~3.8-fold and ~3.2-fold, respectively (both p<0.0001), intracellular glutathione increased ~3.3-fold (p<0.0001), and mitochondrial membrane potential rose ~2.6-fold (p<0.0001). Endothelial injury and adhesion were attenuated (Annexin V ~2-fold↓; ICAM-1 ~33%↓; VCAM-1 ~15%↓; E-selectin ~25%↓; P-selectin ~52%↓; all p<0.0001), while endothelial progenitors and mature endothelial cells increased ~2.4–2.5-fold (both p<0.0001). Pro-inflammatory cytokines IL-1 (p=0.0013), IL-3, IL-6 and TNF-α (all p<0.0001) decreased, whereas IFN-γ increased (p<0.0001) consistent with attenuation of NF-κB-related inflammatory signaling and partial immune reactivation.ConclusionsIron chelation may modulate disease-relevant redox, endothelial, and cytokine pathways in transfusion-dependent MDS, generating mechanistic hypotheses for prospective clinical validation. These findings support the concept that NTBI reduction mitigates pathogenic processes relevant to disease progression, warranting confirmation in prospective studies integrating clinical endpoints.